PERILAKU PETANI DALAM PENGALOKASIAN SUMBERDAYA UNTUK MENCAPAI PENDAPATAN MAKSIMUM DI KECAMATAN SIGI BIROMARU KABUPATEN DONGGALA (Suatu Analisis Linear Programming) - MADE ANTARA (SOCA: Jurnal Sosial Ekonomi Pertanian)
The conversion in the use of rice land to non-agriculture purposes in Sigi BiromaruDistrict increased each year. One initiative of government to increase production in limitedland is intensification and diversification of agriculture. In spite of, the program application isnot evenly distributed in the field. So that, the farmer activity on allocating resourcesoptimally has not been achieved that they did not obtaine a maximum income. The research isaimed: (1) to study a rational of the farmer in a allocating resources, (2) to study a resourcesoptimal allocation, and (3) to observe the respond from a resources optimal allocation of thefarmer household, if there is economic and technical efficiency changes in the agricultureenterprises. Based on the data analysis, it can be concluded that: (1) the farmer in ruralvillage of Pakuli is more rational than farmer in urban village of Jono Oge village, (2)Although both sampled villages have the same resources optimal allocation, but productivityof resources was achieved by farmers in Pakuli higher than farmers in Jono Oge village, (3)maximum income was achieved, if simultaneous changes is made in technical efficiency ,credit ceiling and form products sold (in hulled rice) to encounter input and output pricefluctuation.